Carbonized mangrove wood as photothermal material for solar water desalination - Pandara, Dolfie Paulus; Unso, Kristina; Bobanto, Maria Daurina; Tamuntuan, Gerald Hendrik; Angmalisang, Ping Astony; Ferdy, Ferdy; Tiwow, Vistarani Arini; Kumaunang, Maureen (Institute of Advanced Engineering and Science, 2025)
The investigation into the physical properties of carbonized mangrove wood (CMW) is essential for its development as an efficient solar heat absorber. This study explores the physical characteristics of CMW and its potential application in solar desalination. Initially, the mangrove wood was cleaned with running water, followed by ultrasonication at a frequency of 42 kHz in 96% ethanol for 5 minutes, and then heated at 125 °C for 2 hours. The carbonization process was conducted in a furnace for 1 hour at temperatures of 400, 500, and 600 °C. The physical properties of CMW were analyzed using an X-ray diffractometer (XRD), Fourier transform infrared spectroscopy (FTIR), energy dispersive spectroscopy, and scanning electron microscopy (SEM). The findings revealed the formation of a carbon structure at 2 theta angles of approximately 24.08, 23.26, and 23.16°, with carbon contents of 45.05, 36.86, and 39.37%, respectively. CMW was identified as a porous material, making it highly effective for sunlight absorption in seawater evaporation. The hydroxyl content within the CMW structure enhanced its water evaporation capabilities. In experimental investigations aimed at desalinating seawater, a 300-watt halogen lamp was positioned 15 centimeters above the CMW's surface, resulting in an evaporation rate of 5.33 kg.m-2.h-1. CMW shows significant promise as a solar evaporator.